Justification of specific genetic modifications in pigs for clinical organ xenotransplantation. (15th April 2019) - Cooper, David K. C.; Hara, Hidetaka; Iwase, Hayato; Yamamoto, Takayuki; Li, Qi; Ezzelarab, Mohamed; Federzoni, Elena; Dandro, Amy; Ayares, David
Abstract: Xenotransplantation research has made considerable progress in recent years, largely through the increasing availability of pigs with multiple genetic modifications. We suggest that a pig with nine genetic modifications (ie, currently available) will provide organs (initially kidneys and hearts) that would function for a clinically valuable period of time, for example, >12 months, after transplantation into patients with end‐stage organ failure. The national regulatory authorities, however, will likely require evidence, based on in vitro and/or in vivo experimental data, to justify the inclusion of each individual genetic modification in the pig. We provide data both from our own experience and that of others on the advantages of pigs in which (a) all three known carbohydrate xenoantigens have been deleted (triple‐knockout pigs), (b) two human complement‐regulatory proteins (CD46, CD55) and two human coagulation‐regulatory proteins (thrombomodulin, endothelial cell protein C receptor) are expressed, (c) the anti‐apoptotic and "anti‐inflammatory" molecule, human hemeoxygenase‐1 is expressed, and (d) human CD47 is expressed to suppress elements of the macrophage and T‐cell responses. Although many alternative genetic modifications could be made to an organ‐source pig, we suggest that the genetic manipulations we identify above will all contribute to the success of the initial clinical pig kidney or heart transplants, and that the beneficial contribution of each individual manipulation is supported by considerable experimental evidence.